Blood Component Therapy (Anwer Khan Modern Medical College Journal, 2018)
Transfusion medicine has undergone advancements since its initiation in the early 20th century. One of these was the discovery that blood can be divided into individual components and delivered separately. Today, blood transfusions nearly always consist of the ad-ministration of 1 or more components of blood. Whole blood transfusion is now limited to situations involving massive resuscitation (trauma ) The most familiar cellular components include packed red blood cells (PRBC), washed PRBC, leukoreduced PRBC and pooled or aphaeresis platelets. Plasma products such as FFP or cryoprecipitate, ant hemophilic factor (CRYO). The transfusion of red blood cells (RBCs), platelets, fresh-frozen plasma (FFP), and cryoprecipitate has the potential of improving clinical outcomes in perioperative and peripartum settings. These benefits include improved tissue oxygenation and decreased bleeding. However, transfusions are not without risks or costs. With the advent of blood component therapy, each unit of whole blood collected serves the specific needs of several, rather than a single patient.Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 142-147